Penggunaan Media Gambar Berseri Untuk Meningkatkan Keterampilan Menulis Karangan Dalam Pembelajaran Bahasa Indonesia Pada Siswa Kelas IV SD Negeri 39 Cakranegara - Firdaus, Naviri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This classroom action research aims to improve students' simple essay writing skills through the use of serial picture media. The research method used is classroom action research with a cycle design. The research subjects consisted of 15 grade 4 students at SD Negeri 39 Cakranegara who had low ability to write simple essays. Data were collected through pre- tests, class observations, and interviews. The results showed that the use of serial picture media significantly improved students' simple essay writing skills. Over the course of the research cycle, there was a continuous improvement in students' ability to plan writing, organize ideas, and express thoughts clearly and cohesively. In addition, students also showed increased motivation and interest in writing activities. In conclusion, the use of serial picture media is effective in improving students' simple essay writing skills. This study provides recommendations for teachers to utilize serial picture media as an interesting and useful tool in learning to write simple essays.